Understanding the financial vulnerability and the financial decisions of non-governmental organisations: an empirical study of Ugandan NGOs - Arsenio da Silva, Berta (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.